High-efficiency novel extraction process of target polyphenols using enzymes in hydroalcoholic media - Piazza, Dana Magdalena (2023)
Agro-industrial by-products are a sustainable source of natural additives that can replace the synthetic ones in the food industry. Grape pomace is an abundant by-product that contains about 70% of the grape’s polyphenols. Polyphenols are natural antioxidants with multiple health-promoting properties. They are secondary plant metabolites with a wide range of solubilities. Here, a novel extraction process of these compounds was developed using enzymes that specifically liberates target polyphenols in the appropriate hydroalcoholic mixture. Tannase, cellulase, and pectinase retained 22, 60, and 52% of their activity, respectively, in ethanol 30% v/v. Therefore, extractions were tested in ethanol concentrations between 0 and 30% v/v. Some of these enzymes presented synergistic effects in the extraction of specific polyphenols. Maximum yield of gallic acid was obtained using tannase and pectinase enzymes in ethanol 10% v/v (49.56 ± 0.01 mg L−1 h−1); in the case of p-coumaric acid, by cellulase and pectinase treatment in ethanol 30% v/v (7.72 ± 0.26 mg L−1 h−1), and in the case of trans-resveratrol, by pectinase treatment in ethanol 30% v/v (0.98 ± 0.04 mg L−1 h−1). Also, the effect of enzymes and solvent polarity was analysed for the extraction of malvidin-3-O-glucoside, syringic acid, and quercetin. Previous studies were mainly focused on the maximization of total polyphenols extraction yields, being the polyphenolic profile the consequence but not the driving force of the optimization. In the present study, the basis of a platform for a precise extraction of the desire polyphenols is provided.